Right Ventricular Functional Status in Chronic Obstructive Pulmonary Disease Patient - Ohab, MA; Sarkar, Devendra Nath; Das, Bidhu Bhusan; Sarker, Haripada; Hossain, M Zakir; Islam, Samprity; Alam, Rowshan; Sarkar, Devavrata (Bangladesh Journal of Medicine, 2018)
Aim: To detect the right ventricular status by echocardiography of COPD patients. Background: Chronic obstructive pulmonary disease is an increasing cause of chronic morbidity and mortality worldwide. Smoking is the major cause and the patients consult with physicians very much late when become complicated. Echocardiography is the main determinant of outcome of COPD patient. We can assess the level of pulmonary hypertension which leads to right heart failure. Methods : This is a cross sectional study. Study place was Department of Medicine, Rangpur Medical College from 1st July to 30 September 2014.Clinically and post bronchodilator Spiro metrically diagnosed cases were taken. Patients were graded into Mild, Moderate, severe and very severe categories according to GOLD criteria. Statistical analysis was done with echo findings of RV dilatation and hypertrophy by using Chi-square test and statistical significance was taken as p < 0.05 Results : Mean age was 61.50 (sd±9.76) years with male predominance. Mean duration of disease was 6.80 ( sd ± 4.71) years. Patients had a mean duration of smoking of 23.2 ±3.6 pack years. ECG and Echo findings such as RV dilatation, RV hypertrophy and pulmonary hypertension were showed significant correlation with severity and duration of disease. Diagnosis of cor-pulmonale was clinically 20%, ECG 50% and echocardiographically 92%. Conclusion : COPD is more common in males in 5th to 7th decade with the smoking history of more than 20 pack years. Most patients have moderate to severe disease at presentation. Echocardiography can detect the RV dysfunction in COPD patient earlier. ECG and Echo findings increase as the severity and duration of the disease increases and echocardiography is better than ECG or clinical methods in detecting RV dysfunction. Bangladesh J Medicine Jul 2018; 29(2) : 63-68